DUKUNGAN SOSIAL ORANG TUA, KONSEP DIRI DAN MOTIVASI BERPRESTASI MAHASISWA DI MASA PANDEMI COVID 19 - Amseke, Fredericksen Victoranto; Daik, Marlen Angela; Liu, Doni Ariani Leowandri (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
Motivation achievement is a crucial thing for students during the process of online learning in the pandemic COVID-19 (coronavirus disease) as an ability to encourage an individual to achieve self- actualization and optimal learning outcomes. Motivation achievement is influenced by parental social support as an external factor and self –concepts as an internal factor. Therefore, this research aims to examine the influence of parental social- support and self- concept toward students' motivation achievement in the pandemic COVID-19. This research used a quantitative method. The data were collected using parental social support scale, the self-concept scale and motivation achievement scale. The population in this research consists of 121 freshman year 2020 of Christian Early Childhood Education department in Institute of Christian State Kupang. The sample technique used in this research is accidental sampling with multiple regression analysis. The result proved that parental social support and self-concept have a positive influence and significant toward achievement motivation with 71.8%. Parental social support contributed 23.4% and self-concept contributed 48.4% toward achievement motivation. The higher the role of parents' social support and self-concept, the higher the achievement motivation of students during the pandemic COVID 19. Motivasi berprestasi bagi mahasiswa sangat penting dalam proses pembelajaran daring di masa pandemi COVID-19 (coronavirus disease) sebagai kemampuan yang mendorong individu mencapai aktualisasi diri dan hasil belajar yang optimal. Motivasi berprestasi dipengaruhi oleh dukungan sosial orang tua sebagai faktor eksternal dan faktor internal yaitu konsep diri. Oleh karena itu, penelitian ini bertujuan untuk menguji pengaruh dukungan sosial orang tua dan konsep diri terhadap motivasi berprestasi mahasiswa di masa pandemi COVID-19. Penelitian ini menggunakan metode kuantitatif. Alat pengumpulan data menggunakan skala dukungan sosial orang tua, skala konsep diri dan skala motivasi berprestasi. Partisipan dalam penelitian ini berjumlah 121 mahasiswa pada program studi Pendidikan Kristen Anak Usia Dini di Institut Agama Kristen Negeri Kupang tahun 2020. Teknik analisis data menggunakan analisis regresi berganda. Hasil penelitian ini membuktikan bahwa dukungan sosial orang tua dan konsep diri berpengaruh positif dan signifikan terhadap motivasi berprestasi sebesar 71,8%. Dukungan sosial orang tua berkontribusi 23,4% dan konsep diri berkontribusi 48,4% terhadap motivasi berprestasi. Semakin tinggi peran dukungan sosial orang tua dan konsep diri maka dapat meningkatkan motivasi berprestasi mahasiswa di masa pandemi COVID-19.